Vaping: A Pediatric problem? - Monteiro, Sara; Almeida, Rui (BIRTH AND GROWTH MEDICAL JOURNAL, 2024)
Electronic cigarettes were developed almost two decades ago. Their use, colloquially known as vaping, has gradually increased among young people. Although initially marketed as an alternative to traditional cigarettes, electronic cigarettes expose users to substances associated with adverse health effects and are not recognized by the World Health Organization as a smoking cessation method. The use of new flavors, esthetically appealing devices, and low perceived risk appear to be contributing to increased use among adolescents worldwide, a trend also observed in Portugal. However, their health risks are not fully understood. Recently, a new entity - e-cigarette or vaping-associated lung injury (EVALI) – has been described, with increasing incidence and significant morbimortality. The treatment of nicotine dependence in adolescents who smoke electronic cigarettes is challenging. Electronic cigarettes are addicting a new generation and posing associated health risks. Their increasing use should alert physicians and encourage the development of strategies to address this issue among adolescents.